Continuous magnetron sputtering process for antireflection glass
Through the multi-vacuum chamber continuous magnetron sputtering process, the niobium oxide and silicon oxide layers are plated layer by layer, which solves the problems of low sputtering efficiency and difficult control of film uniformity under high film thickness, and achieves high efficiency and low The wide band reverse effect of cost.
Patent Information
- Application Number
- CN202411639750.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
When the total thickness of the existing coated glass products is greater than 150 nm, there are problems such as low sputtering efficiency, difficult control of film uniformity, and low production efficiency.
The continuous magnetron sputtering process is adopted, and the niobium oxide and silicon oxide layers are coated layer by layer through continuous coating of multiple vacuum chambers, and the film layer thickness is controlled to be above 150nm to improve the sputtering efficiency and film layer uniformity.
The sputtering efficiency of coated glass is improved by about 40%, production cost is reduced by nearly 30%, and a wide-band reverse reaction effect with a film layer thickness greater than 150nm is achieved, with a reflectivity less than 4%, and a visible light transmittance greater than 94%.
Smart Images

Figure CN119461883A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to glass manufacturing technology, in particular to magnetron sputtering coated glass manufacturing technology, specifically to a continuous magnetron sputtering process for anti-reflection glass. Background Art
[0002] Anti-reflective coated glass is a technology that uses magnetron sputtering to deposit one or more layers of thin film materials with specific optical properties on the glass surface under high vacuum conditions to reduce the reflection loss of light and improve the transmittance and optical performance. The main goal of anti-reflective coated glass is to reduce the reflection of light at the interface, thereby increasing the light intensity passing through the glass. Anti-reflective coated glass is used in fields such as construction or automobiles. Its reflectivity is less than 4%, which can greatly reduce light pollution and make the entire visual effect more transparent, fashionable and modern. It is used in the interior decoration of buildings to enhance the decoration grade and taste of the entire building and highlight the modern sense of the building. Anti-reflective glass is used in special places (such as stadiums, museums, etc.), which can effectively avoid the interference of reflected light and is conducive to obtaining clear pictures when filming and shooting.
[0003] At present, in order to make the products more adaptable, anti-reflection coated glass with wide-band anti-reflection effect has been the focus of research and development of various glass manufacturers. Studies have shown that the film structure design of anti-reflection coated glass with wide-band anti-reflection effect is usually more than 150nm thick, but the existing coated glass products have problems such as low sputtering efficiency, difficulty in controlling the uniformity of the film layer, and low production efficiency when the total thickness of the film layer is greater than 150nm. Summary of the invention
[0004] The purpose of the present invention is to provide a continuous magnetron sputtering process for anti-reflection glass, aiming to solve the problems of low sputtering efficiency, difficulty in controlling film uniformity and low production efficiency caused by excessive thickness of a film system with a wide-band anti-reflection effect.
[0005] To achieve the above object, the present invention adopts the following technical solutions: A continuous magnetron sputtering process for anti-reflection glass comprises the following steps: Step S1, sending the cleaned glass substrate into a first vacuum chamber, the atmosphere of the first vacuum chamber is high-purity argon and high-purity oxygen with a flow ratio of 700:800, the sputtering pressure is 1-1.1 Pa, and magnetron sputtering a first niobium oxide layer with a thickness of 12-15 nm is formed on the surface of the glass substrate; Step S2, sending the glass substrate coated with the first niobium oxide layer into the second vacuum chamber and the third vacuum chamber in turn for magnetron sputtering, and coating the first silicon oxide layer with a total thickness of 35-37 nm on the surface of the first niobium oxide layer; the atmosphere of the second vacuum chamber and the third vacuum chamber are both high-purity argon and high-purity oxygen with a flow ratio of 1000:100, and the sputtering pressure is 1-1.1 Pa; Step S3, sending the glass substrate coated with the first silicon oxide layer into the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber in turn for magnetron sputtering, and coating the surface of the first silicon oxide layer with a second niobium oxide layer having a total thickness of 115-127 nm; the atmosphere of the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber are all high-purity argon and high-purity oxygen with a flow ratio of 700:800, and the sputtering pressure is 1-1.1 Pa; Step S4, sending the glass substrate coated with the second niobium oxide layer into the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber in turn for magnetron sputtering, and coating the second silicon oxide layer with a total thickness of 95-105 nm on the surface of the second niobium oxide layer; the atmosphere of the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber are all high-purity argon and high-purity oxygen with a flow ratio of 1000:100, and the sputtering pressure is 1-1.1 Pa; Step S5: post-plating treatment.
[0006] In step S1, the glass substrate is 6 mm white glass; the cathode target of the first vacuum chamber is a niobium oxide target, the sputtering rate is 0.58 nm / min, the sputtering speed is 0.9 m / min, and the sputtering power is 18.6 KW; the thickness of the first niobium oxide layer is 12 nm.
[0007] In step S2, the cathode targets of the second vacuum chamber and the third vacuum chamber are both silicon targets, the sputtering rates are all 0.53 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 18.6 KW; the total thickness of the first silicon oxide layer is 36 nm.
[0008] In step S3, the cathode targets of the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber are all niobium oxide targets, the sputtering rates are all 0.58 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 44.6 KW.
[0009] In the step S3, the sum of the plating thicknesses of the fourth vacuum chamber and the fifth vacuum chamber is less than or equal to the sum of the plating thicknesses of the sixth vacuum chamber and the seventh vacuum chamber.
[0010] In step S4, the cathode targets of the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber are all silicon targets, the sputtering rates are all 0.53 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 53.8 KW.
[0011] In the step S4, the coating thickness of the eighth vacuum chamber is less than or equal to the sum of the coating thicknesses of the ninth vacuum chamber and the tenth vacuum chamber.
[0012] Beneficial effects of the present invention: 1) The reflective coated glass produced is a tempered glass product, which can not only be used as a single piece, but also can be further compounded into laminated, hollow, bent steel and other composite process products.
[0013] 2) The film layer of the product is different from the previous coating products. The film structure used has a wide wide-band anti-reflection effect. The film thickness is greater than 150nm, the reflectivity is less than 4%, and the visible light transmittance is greater than 94%. It is mainly used in photovoltaics, automobiles, high-end buildings, aerospace, display and other fields, with a wide range of applications; 3) The magnetron sputtering process has high sputtering efficiency and good film uniformity control. The sputtering efficiency is increased by about 40%, and the production cost is reduced by nearly 30%. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a flow chart of the present invention.
[0015] Figure 2 This is a diagram of the film structure of the present invention. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be described clearly and completely below in conjunction with the drawings of this specification. It should be noted that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] like Figure 1 , Figure 2 As shown, the present invention provides a continuous magnetron sputtering process for anti-reflection glass, comprising the following steps: Step S1, sending the cleaned glass substrate into a first vacuum chamber, the atmosphere of the first vacuum chamber is high-purity argon and high-purity oxygen with a flow ratio of 700:800, the sputtering pressure is 1-1.1 Pa, and a first niobium oxide layer with a thickness of 12-15 nm is magnetron sputtered on the surface of the glass substrate; in this step, the glass substrate is cleaned by an RF ion source, and there are no other special requirements for cleaning the surface of the glass substrate, so the cleaning process is the existing technology; Step S2, sending the glass substrate coated with the first niobium oxide layer into the second vacuum chamber and the third vacuum chamber in turn for magnetron sputtering, and coating the first silicon oxide layer with a total thickness of 35-37 nm on the surface of the first niobium oxide layer; the atmosphere of the second vacuum chamber and the third vacuum chamber are both high-purity argon and high-purity oxygen with a flow ratio of 1000:100, and the sputtering pressure is 1-1.1 Pa; Step S3, sending the glass substrate coated with the first silicon oxide layer into the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber in turn for magnetron sputtering, and coating the surface of the first silicon oxide layer with a second niobium oxide layer having a total thickness of 115-127 nm; the atmosphere of the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber are all high-purity argon and high-purity oxygen with a flow ratio of 700:800, and the sputtering pressure is 1-1.1 Pa; Step S4, sending the glass substrate coated with the second niobium oxide layer into the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber in turn for magnetron sputtering, and coating the second silicon oxide layer with a total thickness of 95-105 nm on the surface of the second niobium oxide layer; the atmosphere of the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber are all high-purity argon and high-purity oxygen with a flow ratio of 1000:100, and the sputtering pressure is 1-1.1 Pa; Step S5: post-plating treatment.
[0018] The equipment used in the above process is a continuous magnetron sputtering equipment, and the first vacuum chamber to the tenth vacuum chamber are all sputtering chambers of the continuous magnetron sputtering equipment. Among them, a vacuum transition chamber is used between the first vacuum chamber and the second vacuum chamber due to different process parameters. Similarly, a vacuum transition chamber is used between the third vacuum chamber and the fourth vacuum chamber, and a vacuum transition chamber is used between the seventh vacuum chamber and the eighth vacuum chamber. These belong to the existing technology.
[0019] In Example 1 of the present invention, the film thickness calculation and target position configuration included in the above process are shown in Table 1. Table 1: Film thickness calculation and target position configuration
[0020] In Example 1, the glass substrate in step S1 is 6 mm white glass; the cathode target of the first vacuum chamber is a niobium oxide target, the sputtering rate is 0.58 nm / min, the sputtering speed is 0.9 m / min, and the sputtering power is 18.6 KW; the thickness of the first niobium oxide layer is 12 nm.
[0021] In Example 1, in step S2, the cathode targets of the second vacuum chamber and the third vacuum chamber are both silicon targets, the sputtering rate is 0.53nm / min, the sputtering speed is 0.9m / min, and the sputtering power is 18.6KW; the total thickness of the first silicon oxide layer is 36nm. Since the thickness of the first silicon oxide layer is small and easier to control, the coating thickness of the second vacuum chamber and the third vacuum chamber is half of the designed thickness of the first silicon oxide layer.
[0022] In Example 1, in step S3, the cathode targets of the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber are all niobium oxide targets, the sputtering rates are all 0.58 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 44.6 KW.
[0023] In Example 1, in step S3, the sum of the coating thicknesses of the fourth vacuum chamber and the fifth vacuum chamber is less than or equal to the sum of the coating thicknesses of the sixth vacuum chamber and the seventh vacuum chamber. Step S3 adopts multi-chamber continuous coating. In this Example 1, the coating thicknesses of the fourth vacuum chamber, the fifth vacuum chamber and the sixth vacuum chamber are all one-fourth of the designed thickness of the second niobium oxide layer, and the final thickness is precisely controlled in the seventh vacuum chamber; with such a process setting, the uniformity and consistency of the film layer are easy to control, and the sputtering efficiency is effectively improved.
[0024] In Example 1, in step S4, the cathode targets of the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber are all silicon targets, the sputtering rates are all 0.53 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 53.8 KW.
[0025] In Example 1, in step S4, the coating thickness of the eighth vacuum chamber is less than or equal to the sum of the coating thicknesses of the ninth vacuum chamber and the tenth vacuum chamber. In this Example 1, the coating thickness of the eighth vacuum chamber is equal to that of the ninth vacuum chamber, and the final thickness is precisely controlled in the tenth vacuum chamber. With such a process setting, the uniformity and consistency of the film layer are easy to control, and the sputtering efficiency is effectively improved.
[0026] This process has been debugged many times and finally the overall process of this process is obtained. According to this process, the obtained film structure has a wide band anti-reflection effect, the film thickness is greater than 150nm, the reflectivity is less than 4%, and the visible light transmittance is greater than 94%. The application field is wider than the existing technology. For thicker film layers, multi-chamber continuous coating is used to better control the uniformity and consistency of the film layer. At the same time, through the configuration of sputtering rate and sputtering power, the sputtering efficiency is increased by about 40%, and the production cost is reduced by nearly 30%.
[0027] The parts not described in detail in this invention are prior art.
Claims
1. A continuous magnetron sputtering process for anti-reflection glass, characterized by: The following steps are involved: Step S1, sending the cleaned glass substrate into a first vacuum chamber, the atmosphere of the first vacuum chamber is high-purity argon and high-purity oxygen with a flow ratio of 700:800, the sputtering pressure is 1-1.1 Pa, and magnetron sputtering a first niobium oxide layer with a thickness of 12-15 nm is formed on the surface of the glass substrate; Step S2, sending the glass substrate coated with the first niobium oxide layer into the second vacuum chamber and the third vacuum chamber in turn for magnetron sputtering, and coating the first silicon oxide layer with a total thickness of 35-37 nm on the surface of the first niobium oxide layer; the atmosphere of the second vacuum chamber and the third vacuum chamber are both high-purity argon and high-purity oxygen with a flow ratio of 1000:100, and the sputtering pressure is 1-1.1 Pa; Step S3, sending the glass substrate coated with the first silicon oxide layer into the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber in turn for magnetron sputtering, and coating the surface of the first silicon oxide layer with a second niobium oxide layer having a total thickness of 115-127 nm; the atmosphere of the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber are all high-purity argon and high-purity oxygen with a flow ratio of 700:800, and the sputtering pressure is 1-1.1 Pa; Step S4, sending the glass substrate coated with the second niobium oxide layer into the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber in turn for magnetron sputtering, and coating the second silicon oxide layer with a total thickness of 95-105 nm on the surface of the second niobium oxide layer; the atmosphere of the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber are all high-purity argon and high-purity oxygen with a flow ratio of 1000:100, and the sputtering pressure is 1-1.1 Pa; Step S5: post-plating treatment.
2. The continuous magnetron sputtering process for anti-reflection glass according to claim 1, characterized in that: In step S1, the glass substrate is 6 mm white glass; the cathode target of the first vacuum chamber is a niobium oxide target, the sputtering rate is 0.58 nm / min, the sputtering speed is 0.9 m / min, and the sputtering power is 18.6 KW; the thickness of the first niobium oxide layer is 12 nm.
3. The continuous magnetron sputtering process for anti-reflection glass according to claim 1, characterized in that: In step S2, the cathode targets of the second vacuum chamber and the third vacuum chamber are both silicon targets, the sputtering rates are all 0.53 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 18.6 KW; the total thickness of the first silicon oxide layer is 36 nm.
4. The continuous magnetron sputtering process for anti-reflection glass according to claim 1, characterized in that: In step S3, the cathode targets of the fourth vacuum chamber, the fifth vacuum chamber, the sixth vacuum chamber and the seventh vacuum chamber are all niobium oxide targets, the sputtering rates are all 0.58 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 44.6 KW.
5. The continuous magnetron sputtering process for anti-reflection glass according to claim 1, characterized in that: In the step S3, the sum of the plating thicknesses of the fourth vacuum chamber and the fifth vacuum chamber is less than or equal to the sum of the plating thicknesses of the sixth vacuum chamber and the seventh vacuum chamber.
6. The continuous magnetron sputtering process for anti-reflection glass according to claim 1, characterized in that: In step S4, the cathode targets of the eighth vacuum chamber, the ninth vacuum chamber and the tenth vacuum chamber are all silicon targets, the sputtering rates are all 0.53 nm / min, the sputtering speeds are all 0.9 m / min, and the sputtering powers are all 53.8 KW.
7. The continuous magnetron sputtering process for anti-reflection glass according to claim 1, characterized in that: In the step S4, the coating thickness of the eighth vacuum chamber is less than or equal to the sum of the coating thicknesses of the ninth vacuum chamber and the tenth vacuum chamber.
Citation Information
Patent Citations
Magnetron-sputtering filming production system and production process thereof
CN102517553A
Process for producing coral magnetron-sputtering low-emissivity coated glass
CN106116176A
AR and AF film layer structure and AR and AF coated glass product
CN118084349A
Corrosion-resistant heat insulation type LOW-E glass
CN209259940U